Therapeutic Benefits of Pomegranate Flower Extract: A Novel Effect That Reduces Oxidative Stress and Significantly Improves Diastolic Relaxation in Hyperglycemic In Vitro in Rats. (8th June 2022) - Wei, Yuanyuan; Khalaf, Ahmad Taha; Ye, Peng; Fan, Wei; Su, Junyi; Chen, Wanlu; Hu, Hao; Menhas, Rashid; Wang, Lifeng; Oglah, Zahraa
Abstract : The pomegranate flower is an ancient herb in traditional Chinese medicine with multiple properties. Recent studies have shown that pomegranate flower extract is beneficial, especially for hyperglycemia. In this experiment, we investigated the diastolic effect of pomegranate flower polyphenol (PFP) extract on the isolated thoracic aorta of rats in both the absence and presence of high glucose levels. Isotonic contractile forces were recorded from aortic rings (about 3 mm in length) from rats using the BL-420F Biological Function Test System. Tissues were precontracted with 60 mM KCl to obtain maximum tension under 1.0 g load for 1 hour before the balance was achieved, and the fluid was changed every 15 minutes. PFP (700 mg/L–900 mg/L) showed a concentration-dependent relaxant effect on the aortic rings; vasodilation in the endothelium-intact was significantly higher than that in the de-endothelialized segments P < 0.01 . The endothelium-dependent vasorelaxant effect of PFP was partially attenuated by K + channel blockers, tetraethylammonium (TEA), glibenclamide (Glib), and BaCl2, as well as L-NAME (eNOS inhibitor) on the denuded endothelium artery ring. Concentration-dependent inhibition of PFP on releasing intracellular Ca 2+ in the Ca 2+ -free solution and vasoconstriction of CaCl2 in Ca 2+ -free buffer plus K + (60 mM) was observed. In addition, PFP (0.1–10 mg/L) showed significant inhibition of acetylcholine-induced endothelial-dependent relaxation in the aorta of rats in the presence of high glucose (44 mmol/L). Nevertheless, the vasodilating effect of PFP was inhibited by atropine and L-NAME. The results indicated that PFP-induced vasodilation was most likely related to the antioxidant effects through enhanced NO synthesis, as well as the blocking of K + channels and inhibition of extracellular Ca 2+ entry. In conclusion, these observations showed that PFP ameliorates vasodilation in hyperglycemic rats. Hence, our results suggest that PFP supplementation may be beneficial for hypertensive patients with diabetes.